Three-dimensional computed tomography reconstruction in video-assisted thoracoscopic segmentectomy (DRIVATS): A prospective, multicenter randomized controlled trial - Niu, Zhenyi; Chen, Kai; Jin, Runsen; Zheng, Bin; Gong, Xian; Nie, Qiang; Jiang, Benyuan; Zhong, Wenzhao; Chen, Chun; Li, Hecheng (Frontiers in Surgery, 2022)
Objective: Anatomical segmentectomy has been proven to be a viable surgical treatment for small-size peripheral lung nodules. Three-dimensional (3D) reconstruction computed tomography (CT) has been proposed as an effective approach to overcome the challenges of encountering pulmonary anatomical variations when performing segmentectomy. Therefore, to further investigate the usefulness of preoperative 3D reconstruction CT in segmentectomy, we will conduct this prospective, multicenter randomized controlled DRIVATS study to compare the use of 3D reconstruction CT with standard chest CT in video-assisted segmentectomy (ClinicalTrials.gov ID: NCT04004494). Methods: This study began in July 2019 and a total of 190 patients will be accrued from three clinical centers within four years. The main inclusion criteria are patients with single peripheral nodule 0.8-2 cm with at least one of the following requirements: i. histology of adenocarcinoma in situ, ii. nodule has ≥50% ground-glass appearance on CT, iii. radiologic surveillance confirms a long doubling time (≥400 days). Surgical procedures include segmental resection of the lesion and mediastinal lymph node sampling (subsegmental resection or combined subsegmental resection will not be included in this study). Results: The primary endpoint is operative time. The secondary endpoints are incidence of change of surgical plan, intraoperative blood loss, conversion rate, operative accident event, incidence of postoperative complications, postoperative hospital stay, length of hospitalization, duration of chest tube placement, postoperative 30-day mortality, dissection of lymph nodes, overall survival, disease-free survival, preoperative lung function, postoperative lung function. Conclusions: This multicenter DRIVATS study will further investigate and provide higher-level of evidence for the use of 3D reconstruction CT in segmentectomy.